Concept of primary eye care & school health in India - Anjan Kumar Giri; Sunita Behera; Abhiruchi Galhotra (Wolters Kluwer Medknow Publications, 2018)
Primary eye care consists of promotive, preventive and curative actions by trained personnel or other interested people. Teachers are the best manpower to be trained for this purpose since they are more close to the students always. Poor visual function during early childhood may have several adverse outcomes. Through the school children, health messages can be propagated to their families, friends and peer groups. Training school teachers and empowering students and other staff of the school on simple and safe eye care practices through organized activities may come out as a cost effective way of improving general health and academic performance.